High-voltage positive electrode material precursor, preparation method thereof and high-voltage positive electrode material
By adding chromium elements into spinel-type lithium nickel manganate and using co-precipitation method to prepare the precursor of high-voltage positive electrode material, the structural distortion and capacity attenuation caused by the conversion of Mn4+ to Mn3+ are solved, and the structural stability and cyclic stability of high-voltage positive electrode material are improved.
Patent Information
- Application Number
- CN202411890442.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
AI Technical Summary
During the synthesis process, some Mn4+ ions of spinel-type lithium nickel manganate are converted to Mn3+, resulting in structural distortion, capacity attenuation and cycle stability.
The high-voltage positive electrode material precursor was prepared by co-precipitation method. By adding chromium elements into the nickel-manganese binary precursor, NixMn1-xCryO4 structure was formed to increase the surface area and structural stability.
It improves the charge and discharge voltage and cycle stability of high-voltage positive electrode materials, extends the cycle life of the battery, and improves the capacity retention rate.
Smart Images

Figure CN119706970A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a high-voltage positive electrode material precursor and a preparation method thereof, and a high-voltage positive electrode material. Background Art
[0002] Spinel lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4, LNMO) materials are currently the positive electrode materials for lithium-ion batteries with the highest output voltage, low cost, and environmental friendliness, and are increasingly favored as cobalt-free cathode materials. However, due to the fact that some Mn 4+ The ion will transform into Mn 3+ ions. Due to Mn 3+ Not only will the Jahn-Teller distortion effect occur, causing lattice distortion and structural collapse, but also some Mn 3+ Ions undergo disproportionation reactions (2Mn 3+ →Mn 2+ +Mn 4+ ), the generated Mn 2+ Ions will dissolve in the electrolyte, causing a reduction in active substances, accelerating structural collapse, and causing serious capacity decay. Summary of the invention
[0003] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a high-voltage positive electrode material precursor and a preparation method thereof and a high-voltage positive electrode material.
[0004] The present invention provides a high voltage positive electrode material precursor, which comprises a plurality of secondary particles formed by combining primary nanosheets, and the composition is Ni x Mn 1-x Cr y O4, where 0.05≤x≤0.30, 0≤y≤0.01.
[0005] The present invention also provides a method for preparing the above-mentioned high-voltage positive electrode material precursor, comprising: using NaOH solution and Na2CO3 solution as precipitants and adopting a co-precipitation method to prepare the high-voltage positive electrode material precursor.
[0006] The present invention also provides a high-voltage positive electrode material, which is obtained by mixing and sintering the high-voltage positive electrode material precursor and a lithium source.
[0007] The present invention has the following beneficial effects: The present invention provides a high-voltage positive electrode material precursor and a preparation method thereof and a high-voltage positive electrode material. The high-voltage positive electrode material precursor provided by the present invention comprises a plurality of secondary particles formed by combining primary nanosheets, and the composition thereof is Ni x Mn 1-x Cr y O4, wherein 0.05≤x≤0.30, 0≤y≤0.01. The high-voltage positive electrode material precursor provided above not only has a special morphology but also adds chromium element, which can increase the surface area, shorten the ion path transmission distance, increase the structural stability of the high-voltage positive electrode material prepared by the high-voltage positive electrode material precursor, and improve the charge and discharge voltage and cycle stability of the high-voltage positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0009] Figure 1 This is a SEM image of the high voltage positive electrode material precursor prepared in Example 1; Figure 2 This is a SEM image of the high voltage positive electrode material precursor prepared in Example 2; Figure 3 This is a SEM image of the high voltage positive electrode material precursor prepared in Comparative Example 1; Figure 4 This is a SEM image of the high voltage positive electrode material precursor prepared in Comparative Example 2; Figure 5 This is the SEM image of the high voltage positive electrode material precursor prepared in Comparative Example 3. DETAILED DESCRIPTION
[0010] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0011] A high-voltage positive electrode material precursor and a preparation method thereof and a high-voltage positive electrode material provided in an embodiment of the present invention are specifically described below.
[0012] In a first aspect, an embodiment of the present invention provides a high voltage positive electrode material precursor, the high voltage positive electrode material precursor comprises a plurality of secondary particles formed by combining primary nanosheets, the composition of which is Ni x Mn 1-x Cr y O4, where 0.05≤x≤0.30, 0≤y≤0.01.
[0013] The spinel nickel manganese oxide currently prepared will have serious capacity decay. According to analysis, the discharge platform of nickel manganese oxide is around 4.7V and can reach a maximum of 5.2V, while the mainstream LiPF6 electrolyte on the market can only maintain reliable stability at a maximum of around 4.5V. The main reason for its capacity decay is the side reaction between the positive electrode material and the electrolyte under high voltage, which causes serious capacity decay under high voltage conditions.
[0014] The embodiment of the present invention provides a high voltage positive electrode material precursor, which improves the electrochemical performance of the positive electrode material by synthesizing a precursor with a special structure, and at the same time, Cr is added to the high voltage positive electrode material precursor to stabilize the material structure and reduce Mn 3+ The generation of ions can reduce the side reaction between the high-voltage positive electrode material prepared by the high-voltage positive electrode material precursor and the electrolyte, increase the discharge platform voltage of the high-voltage positive electrode material, and further increase the charge and discharge capacity and cycle stability of the high-voltage positive electrode material.
[0015] In some optional embodiments, the secondary particles are spherical or quasi-spherical particles formed by orderly stacking or disordered cross-aggregation of primary nanosheets, and the thickness of the primary nanosheets is 280 nm-290 nm.
[0016] In some optional embodiments, the particle size of the high voltage positive electrode material precursor is 2 μm-10 μm.
[0017] In a second aspect, an embodiment of the present invention further provides a method for preparing the above-mentioned high-voltage positive electrode material precursor, comprising: using NaOH solution or Na2CO3 solution as a precipitant and ammonia water as a complexing agent, and adopting a co-precipitation method to prepare the high-voltage positive electrode material precursor.
[0018] An embodiment of the present invention provides a method for preparing the above-mentioned high-voltage positive electrode material precursor. In the wet synthesis stage, two precipitants are introduced simultaneously in a specific ratio to synthesize a nickel-manganese binary precursor with a special thin sheet structure. The structure has the advantages of a large specific surface area and a short ion path transmission distance, and can improve the electrochemical properties of the material. At the same time, by adding chromium element in the wet synthesis stage, the chromium element can be uniformly incorporated into the nickel-manganese binary precursor with a special thin sheet structure, thereby improving the stability of the high-voltage positive electrode material precursor and further improving product performance.
[0019] In some optional embodiments, the steps include: adding deionized water into the reactor, introducing nitrogen gas for air replacement and then starting stirring, adjusting the pH value and ammonia concentration to the required values to obtain the required base liquid, and adding nickel-manganese mixed salt solution, NaOH solution, Na2CO3 solution, ammonia solution, and chromium salt solution into the reactor in parallel in proportion to carry out a co-precipitation reaction, and continuing the reaction until a high-voltage positive electrode material precursor with a required particle size is obtained.
[0020] In some optional embodiments, the concentration of the nickel-manganese mixed salt solution is 1mol / L-3mol / L, the concentration of the NaOH solution is 1mol / L~15mol / L, the concentration of the Na2CO3 solution is 0.1mol / L~15mol / L, the molar ratio of Na2CO3 in the Na2CO3 solution to NaOH in the NaOH solution is (0.05~0.15):1, the concentration of the ammonia solution is 5mol / L~10mol / L, and the concentration of the chromium salt solution is 0.1mol / L-1mol / L.
[0021] The embodiment of the present invention provides a method for preparing a high-voltage positive electrode material precursor. The inventor found that: in the wet synthesis stage, two precipitants Na2CO3 and NaOH are introduced simultaneously in a specific ratio to synthesize a nickel-manganese binary precursor with a special thin-sheet structure. This is because only NaOH is used as a precipitant, and the prepared high-voltage positive electrode material precursor presents a large block morphology. By introducing a small amount of Na2CO3 to form a carbonate precipitate during the coprecipitation process, the morphology can be changed, and the molar ratio of Na2CO3 to NaOH is 0.05~0.15:1, which is more suitable. If the molar ratio of sodium carbonate to sodium hydroxide is lower than 0.05, the effect on the final morphology is low. If the molar ratio is higher than 0.15, the final morphology is prone to significant changes, and is more inclined to carbonate precipitation. If the pH value of the reaction system is lower than 10, it is not conducive to the generation of crystal nuclei of the product; if it is higher than 13, it is not conducive to the agglomeration of crystal nuclei of the product and the formation of carbonate precipitation.
[0022] In some optional embodiments, the pH of the base solution is controlled to be 10-13, and the ammonium ion concentration is controlled to be 0.1 mol / L-2 mol / L.
[0023] In some optional embodiments, the stirring rate of the mixed solution in the reactor is controlled to be 200 rpm~1200 rpm, and the temperature is 40°C~80°C. After the co-precipitation reaction is completed, the obtained slurry is filtered to obtain a filter cake, and the filter cake is then centrifuged, washed, dried, sieved, demagnetized, and mixed to obtain a high-voltage positive electrode material precursor.
[0024] In a third aspect, an embodiment of the present invention further provides a high voltage positive electrode material, which is obtained by mixing and sintering the above-mentioned high voltage positive electrode material precursor with a lithium source.
[0025] In some optional embodiments, the discharge platform of the high voltage positive electrode material is 4.9V-5.2V, and the capacity retention rate of the product after 100 cycles is above 93%.
[0026] The embodiment of the present invention also provides a high-voltage positive electrode material, which is synthesized by synthesizing a high-voltage positive electrode material precursor having a special thin-sheet structure and adding chromium elements. The structure of the high-voltage positive electrode material precursor has the advantages of large specific surface area and short ion path transmission distance, thereby improving the electrochemical performance of the high-voltage positive electrode material prepared by the high-voltage positive electrode material precursor. After the discharge platform of the high-voltage positive electrode material is increased from 4.7V to 4.9V, the capacity retention rate after 100 cycles is above 93%.
[0027] The present invention will be further described below in conjunction with the embodiments.
[0028] Example 1: Preparation of a chromium-doped high-voltage cathode material precursor having a special thin-sheet structure (1) First, nickel sulfate and manganese sulfate are prepared into a mixed solution with a concentration of 2.0 mol / L using deionized water.
[0029] (2) Prepare a solution of NaOH precipitant with deionized water at a concentration of 10.0 mol / L.
[0030] (3) Use deionized water to prepare a solution of Na2CO3 precipitant with a concentration of 3.0 mol / L.
[0031] (4) Dilute the ammonia solution to 9.0 mol / L with deionized water and set aside.
[0032] (5) Use deionized water to prepare a 0.2 mol / L solution of chromium salt.
[0033] (6) Deionized water is added to the reactor, and nitrogen is introduced to replace the air, and then stirring is started. The pH value and ammonia concentration are adjusted to the required values to obtain the required bottom liquid. According to the required proportion of the product, the solutions (1), (2), (3), (4), and (5) are continuously added to the bottom liquid of the reactor at a certain flow rate. According to the test results, the flow rate of (2) can be adjusted to stabilize the reaction atmosphere. When adjusting the flow rate of (2), the flow rate of (3) is adjusted proportionally to keep the ratio of the amount of (2) and (3) introduced consistent. The reaction is continued until the required particle size is obtained, and the reaction is stopped.
[0034] (7) The slurry obtained by the coprecipitation reaction is filtered to form a filter cake, and then the filter cake is centrifuged, washed, dried, screened, demagnetized, and mixed to obtain a chromium-doped nickel-manganese binary positive electrode material precursor product with a special structure.
[0035] in: The above product Ni:Mn=1:3; The above product (Ni+Mn): Cr=0.99:0.01; The particle size of the above product is 8.0 μm; The stirring rate is 700 rpm; The temperature in the above kettle is stably controlled to be 80°C; The pH control range of the above-mentioned base solution is 10.0~13.0; The above Na2CO3:NaOH=0.10:1 The above-mentioned base liquid ammonium ion concentration is controlled in the range of 0.1~2mol / L; Example 2: Preparation of a chromium-doped high-voltage cathode material precursor having a special thin-sheet structure (1) First, nickel sulfate and manganese sulfate are prepared into a mixed solution with a concentration of 2.0 mol / L using deionized water.
[0036] (2) Prepare a solution of NaOH precipitant with deionized water at a concentration of 10.0 mol / L.
[0037] (3) Use deionized water to prepare a solution of Na2CO3 precipitant with a concentration of 3.0 mol / L.
[0038] (4) Dilute the ammonia solution to 9.0 mol / L with deionized water and set aside.
[0039] (5) Use deionized water to prepare a 0.2 mol / L solution of chromium salt.
[0040] (6) Deionized water is added to the reactor, and nitrogen is introduced to replace the air and then stirring is started. The pH value and ammonia concentration are adjusted to the required values to obtain the required bottom liquid. According to the required proportion of the product, the solutions (1), (2), (3), (4), and (5) are continuously added to the bottom liquid of the reactor at a certain flow rate. According to the test results, the flow rate of (2) can be adjusted to stabilize the reaction atmosphere. When adjusting the flow rate of (2), the flow rate of (3) is adjusted proportionally to keep the ratio of the amount of (2) and (3) introduced consistent, and the reaction is continued until the product with the required particle size is obtained.
[0041] (7) The slurry obtained by the coprecipitation reaction is filtered to form a filter cake, and then the filter cake is centrifuged, washed, dried, screened, demagnetized, and mixed to obtain a chromium-doped nickel-manganese binary positive electrode material precursor with a special structure.
[0042] in: The above product Ni:Mn=1:4; The above product (Ni+Mn): Cr=0.992:0.008; The particle size of the above product is 6.0 μm; The stirring rate is 700 rpm; The temperature in the above kettle is stably controlled to be 60°C; The pH control range of the above-mentioned base solution is 10.0~13.0; The above Na2CO3:NaOH=0.15:1 The above-mentioned base liquid ammonium ion concentration is controlled in the range of 0.1~2mol / L; Comparative Example 1: The difference between this comparative example and Example 1 is that only chromium-doped high-voltage positive electrode material precursor is prepared. (1) First, nickel sulfate and manganese sulfate are prepared into a mixed solution with a concentration of 2.0 mol / L using deionized water.
[0043] (2) Prepare a solution of NaOH precipitant with deionized water at a concentration of 10.0 mol / L.
[0044] (3) Use deionized water to prepare a solution of Na2CO3 precipitant with a concentration of 3.0 mol / L.
[0045] (4) Dilute the ammonia solution to 9.0 mol / L with deionized water and set aside.
[0046] (5) Use deionized water to prepare a 0.2 mol / L solution of chromium salt.
[0047] (6) Deionized water is added to the reactor, nitrogen is introduced for air replacement, and stirring is started. The pH value and ammonia concentration are adjusted to the required values to obtain the required base liquid. The solutions (1), (2), (4), and (5) are continuously added to the base liquid of the reactor at a certain flow rate according to the required proportion of the product. According to the test results, the flow rate of (2) can be adjusted to stabilize the reaction atmosphere. The reaction is continued until the product with the required particle size is obtained.
[0048] (7) The slurry obtained by the coprecipitation reaction is filtered to form a filter cake, and then the filter cake is centrifuged, washed, dried, sieved, demagnetized, and mixed to obtain a chromium-doped nickel-manganese binary positive electrode material precursor.
[0049] in: The above product Ni:Mn=1:3; The above product (Ni+Mn): Cr=0.99:0.01; The particle size of the above product is 8.0 μm; The stirring rate is 700 rpm; The temperature in the above kettle is stably controlled to be 80°C; The pH control range of the above-mentioned base solution is 10.0~13.0; The above-mentioned base liquid ammonium ion concentration is controlled in the range of 0.1~2mol / L; Comparative Example 2: The difference between this comparative example and Example 1 is that a high voltage positive electrode material precursor having only a special flaky structure is prepared. (1) First, nickel sulfate and manganese sulfate are prepared into a mixed solution with a concentration of 2.0 mol / L using deionized water.
[0050] (2) Prepare a solution of NaOH precipitant with deionized water at a concentration of 10.0 mol / L.
[0051] (3) Use deionized water to prepare a solution of Na2CO3 precipitant with a concentration of 3.0 mol / L.
[0052] (4) Dilute the ammonia solution to 9.0 mol / L with deionized water and set aside.
[0053] (5) Use deionized water to prepare a 0.2 mol / L solution of chromium salt.
[0054] (6) Deionized water is added to the reactor, and nitrogen is introduced to replace the air and then stirring is started. The pH value and ammonia concentration are adjusted to the required values to obtain the required bottom liquid. According to the required proportion of the product, the solutions (1), (2), (3), and (4) are continuously added to the bottom liquid of the reactor at a certain flow rate. According to the test results, the flow rate of (2) can be adjusted to stabilize the reaction atmosphere. When adjusting the flow rate of (2), the flow rate of (3) is adjusted proportionally to keep the ratio of the amount of (2) and (3) introduced consistent, and the reaction is continued until the product with the required particle size is obtained.
[0055] (7) The slurry obtained by the coprecipitation reaction is filtered to form a filter cake, and then the filter cake is centrifuged, washed, dried, screened, demagnetized, and mixed to obtain a nickel-manganese binary positive electrode material precursor with a special structure.
[0056] in: The above product Ni:Mn=1:3; The particle size of the above product is 8.0 μm; The stirring rate is 700 rpm; The temperature in the above kettle is stably controlled to be 80°C; The pH control range of the above-mentioned base solution is 10.0~13.0; The above Na2CO3:NaOH=0.10:1 The above-mentioned base liquid ammonium ion concentration is controlled in the range of 0.1~2mol / L; Comparative Example 3: The difference between this comparative example and Example 1 is that a high voltage positive electrode material precursor without a special flake structure and without chromium doping is prepared. (1) First, nickel sulfate and manganese sulfate are prepared into a mixed solution with a concentration of 2.0 mol / L using deionized water.
[0057] (2) Prepare a solution of NaOH precipitant with deionized water at a concentration of 10.0 mol / L.
[0058] (3) Use deionized water to prepare a solution of Na2CO3 precipitant with a concentration of 3.0 mol / L.
[0059] (4) Dilute the ammonia solution to 9.0 mol / L with deionized water and set aside.
[0060] (5) Use deionized water to prepare a 0.2 mol / L solution of chromium salt.
[0061] (6) Deionized water is added to the reactor, nitrogen is introduced for air replacement, and stirring is started. The pH value and ammonia concentration are adjusted to the required values to obtain the required base liquid. The solutions (1), (2), and (4)) are continuously added to the reactor at a certain flow rate according to the required proportion of the product. According to the test results, the flow rate of (2) can be adjusted to stabilize the reaction atmosphere. The reaction is continued until the product with the required particle size is obtained.
[0062] (7) The slurry obtained by the coprecipitation reaction is filtered to form a filter cake, and then the filter cake is centrifuged, washed, dried, screened, demagnetized, and mixed to obtain a chromium-doped nickel-manganese binary positive electrode material precursor with a special structure.
[0063] in: The above product Ni:Mn=1:3; The particle size of the above product is 8.0 μm; The stirring rate is 700 rpm; The temperature in the above kettle is stably controlled to be 80°C; The pH control range of the above-mentioned base solution is 10.0~13.0; The above-mentioned bottom solution ammonium ion concentration is controlled in the range of 0.1~2mol / L Performance Testing 1. The precursors prepared in Example 1, Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 and lithium hydroxide were uniformly mixed in a molar ratio of 1:1.02, sintered at 750°C in an oxygen atmosphere for 10 h, and then taken out and ground to finally obtain three positive electrode materials, which were respectively recorded as A1, A2, B1, B2 and B3.
[0064] 2. Mix the five positive electrode materials A1, A2, B1, B2 and B3 into slurry according to the ratio of positive electrode material: conductive carbon: polyvinylidene fluoride (PVDF) = 90:5:5 to make positive electrode sheets (the compaction density of the sheet is 3.3g / cm 2 , lithium metal sheets are selected as the negative electrode material and assembled into 2025 button batteries.
[0065] 3. Using 1MLiPF6 / EC:DEC:DMC=1:1:1 (V%) as the electrolyte (EC is ethylene carbonate, DEC is diethyl carbonate, and DMC is dimethyl carbonate), after three cycles of activation at a rate of 0.2C, the battery was cycled 100 times at a rate of 0.2C. The discharge capacity at the 1st cycle and the discharge capacity at the 100th cycle were measured, and the capacity retention rate after 100 cycles was calculated.
[0066] Capacity retention rate after 100 cycles (%) = discharge capacity at the 100th cycle / discharge capacity at the 1st cycle × 100%, the specific capacity and cycle retention rate of the material are obtained, as shown in Table 1 below.
[0067] Table 1 Comparison of electrical properties of positive electrode materials obtained in Examples and Comparative Examples
[0068] It can be seen from Table 1 above that the battery further prepared by using the high voltage positive electrode material precursor prepared in the embodiment of the present application can have a higher specific capacity and capacity retention rate than the comparative example at a high voltage platform of 5.0V. Figure 1 -Attached Figure 5 It can be seen that the high-voltage positive electrode material precursor with a special structure and doped with chromium prepared in the present application has a more slender morphology, which is significantly different from the ordinary precursor.
[0069] It can be seen from the above results that the preparation method of the above-mentioned high-voltage positive electrode material precursor provided by the embodiment of the present invention, during the synthesis process of the high-voltage positive electrode material precursor, sodium carbonate and sodium hydroxide solution are introduced simultaneously, and the amount of the two introduced is controlled to form a special thin sheet structure in the product. At the same time, the high-voltage positive electrode material precursor is doped with chromium, so as to improve the electrochemical properties of the material while improving the discharge platform voltage. If only chromium doping is performed, the cycle capacity retention rate of the battery can be significantly improved, but the degree of improvement in specific capacity is low. If only special thin sheet structure treatment is performed, the specific capacity of the battery can be significantly improved, but the improvement in the cycle capacity retention rate of the product is low. After chromium doping and special thin sheet structure modification, the specific capacity and cycle capacity retention rate of the battery can be significantly improved.
[0070] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high voltage positive electrode material precursor, characterized in that: The high voltage positive electrode material precursor comprises a plurality of secondary particles formed by combining primary nanosheets, and the composition is Ni x Mn 1-x Cr y O4, where 0.05≤x≤0.30, 0≤y≤0.
01.
2. The high voltage positive electrode material precursor according to claim 1, characterized in that: The secondary particles are spherical or quasi-spherical particles formed by orderly stacking or disordered cross-aggregation of primary nanosheets, and the thickness of the primary nanosheets is 280nm-290nm.
3. The high voltage positive electrode material precursor according to claim 1, characterized in that: The particle size of the high voltage positive electrode material precursor is 2 μm-10 μm.
4. A method for preparing a high voltage positive electrode material precursor according to any one of claims 1 to 3, characterized in that: include: The high voltage positive electrode material precursor is prepared by co-precipitation method using NaOH solution and Na2CO3 solution as precipitants and ammonia water as complexing agent.
5. The preparation method according to claim 4, characterized in that: The method comprises the following steps: adding deionized water into a reaction kettle, introducing nitrogen gas for air replacement and then starting stirring, adjusting the pH value and ammonia concentration to required values to obtain the required base liquid, adding a nickel-manganese mixed salt solution, a NaOH solution, a Na2CO3 solution, an ammonia solution and a chromium salt solution into the reaction kettle in parallel in proportion to carry out a coprecipitation reaction, and continuing the reaction until a high-voltage positive electrode material precursor with a required particle size is obtained.
6. The preparation method according to claim 5, characterized in that: The concentration of the nickel-manganese mixed salt solution is 1mol / L-3mol / L, the concentration of the NaOH solution is 1mol / L~15mol / L, the concentration of the Na2CO3 solution is 0.1mol / L~15mol / L, the molar ratio of Na2CO3 in the Na2CO3 solution to NaOH in the NaOH solution is (0.05~0.15):1, the concentration of the ammonia solution is 5mol / L~10mol / L, and the concentration of the chromium salt solution is 0.1mol / L-1mol / L.
7. The preparation method according to claim 5, characterized in that: The pH of the base solution is controlled to be 10-13, and the ammonium ion concentration is controlled to be 0.1 mol / L-2 mol / L.
8. The preparation method according to claim 5, characterized in that: The stirring rate of the mixed solution in the reactor is controlled to be 200 rpm~1200 rpm, and the temperature is controlled to be 40°C~80°C. After the coprecipitation reaction is completed, the obtained slurry is filtered to obtain a filter cake, and then the filter cake is centrifuged, washed, dried, sieved, demagnetized, and mixed to obtain the high-voltage positive electrode material precursor.
9. A high voltage positive electrode material, characterized in that: The high voltage positive electrode material is obtained by mixing and sintering a high voltage positive electrode material precursor according to any one of claims 1 to 3 or a high voltage positive electrode material precursor prepared by the preparation method according to any one of claims 4 to 8 with a lithium source.
10. The high voltage positive electrode material according to claim 9, characterized in that: The discharge platform of the high voltage positive electrode material is 4.9V-5.2V, and the capacity retention rate after 100 cycles is above 93%.